واقع مخابر البحث العلمي في الجامعة ومقترحات تطويرها -حسب رأي عينة من أساتذة العلوم الاجتماعية - فلوح, أحمد (جامعة الوادي - University of Eloued, 2018)
استهدفت الدراسة التعرف على واقع مخابر البحث العلمي في الجامعة الجزائرية ومقترحات تطويرها من وجهة نظر عينة من أساتذة العلوم الإنسانية والاجتماعية بالمركز الجامعي غليزان. ولتحقيق أهداف الدراسة تم إعداد استبيان يتكون من 46 عبارة موزعة على أربعة أبعاد وزعت على عينة من الأساتذة ينتمون لتخصصات العلوم الاجتماعية والإنسانية وتوصلت الدراسة الى أن مخابر البحث العلمي في وضعية غير مرضية، وان دورها ومساهمتها ضعيفة في التنمية، وان هناك عواقب وخيمة على الباحث والجامعة والمجتمع نتيجة ضعف مخابر البحث، ولقد قدم الأساتذة أفراد عينة الدراسة مجموعة من الاقتراحات لتطوير مخابر البحث العلمي.The study aimed to identify the reality of scientific research laboratories in the Algerian University and the proposals to develop them from the point of view of a sample of professors of humanities and social sciences at the University Center of Relizane. In order to achieve the objectives of the study, a questionnaire was prepared consisting of 46 words distributed over four dimensions distributed to a sample of professors belonging to the social and human sciences disciplines. The study concluded that the scientific research laboratories are in an unsatisfactory situation, and that there are serious consequences for the researcher and the university and society as a result of weak research laboratories, and the professors gave the members of the study sample a set of suggestions for the development of scientific research laboratories.
The reality of scientific research laboratories in the university and proposals for its development (According to the opinion of a sample of social science professors)
مقال
Keywords: الجامعة الجزائرية، البحث العلمي، مخابر البحث; Algerian University - Scientific Research - Research Laboratories